2019
DOI: 10.21834/e-bpj.v4i12.1902
|View full text |Cite
|
Sign up to set email alerts
|

“H.O.P.E.” Hold On Pain Ends: Effects of Reminiscence Therapy on Depression for Elderly with Alzheimer’s Disease

Abstract: Elderly with Alzheimer's disease may experience various adverse effects on physical and psychological functions, especially depression level. Effective intervention may reduce depressive symptoms. Therefore, the current study aims to investigate the effect of individualized reminiscence therapy on depression levels among the elderly with Alzheimer's disease. The findings showed that individualized-reminiscence therapy significantly affects the elderly with Alzheimer's depression level. In conclusion, reminisce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Duru Asiret and Kapucu (2016) studied the effects of group reminiscence on the cognitive status, depression, and daily activities of patients with mild to moderate Alzheimer's disease and found a significant improvement in cognitive status (about 3 points increase in the mean SMMSE score), decrease in depression and increase in quality of life. Reminiscence therapy is potentially effective in maintaining cognition and decreasing depressive symptomatology (Azizan et al, 2019; Gil et al, 2019). Reminiscence interventions have demonstrated improvements in depressive symptoms, well‐being, peace and life satisfaction, quality of life, social engagement, anxiety, and cognitive skills/memory (Shropshire, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Duru Asiret and Kapucu (2016) studied the effects of group reminiscence on the cognitive status, depression, and daily activities of patients with mild to moderate Alzheimer's disease and found a significant improvement in cognitive status (about 3 points increase in the mean SMMSE score), decrease in depression and increase in quality of life. Reminiscence therapy is potentially effective in maintaining cognition and decreasing depressive symptomatology (Azizan et al, 2019; Gil et al, 2019). Reminiscence interventions have demonstrated improvements in depressive symptoms, well‐being, peace and life satisfaction, quality of life, social engagement, anxiety, and cognitive skills/memory (Shropshire, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A diverse number of studies have shown the benefits of RT. Some of the important outcomes include the decrease of negative side-effects such as, depression, aggression and anxiety [7]; higher patient adaptation towards to the present time and life satisfaction [8], [9], and improvements in cognitive performance [10].…”
Section: Introductionmentioning
confidence: 99%